Fault-Tolerant Prescribed Performance Attitude Tracking Control for Spacecraft Under Input Saturation - Shao, Xiaodong; Hu, Qinglei; Shi, Yang; Jiang, Boyan (IEEE transactions on control systems technology, 2020)
This brief examines the problem of attitude tracking control with prescribed performance guarantees for a spacecraft subjected to actuator faults and input saturation. To pursue this, the open-loop tracking error dynamics with certain designer-specified performance constraints is first transformed into an equivalent "state-constrained" one, via an error transformation; furthermore, the resulting dynamics is augmented with a dynamic system, which is tactfully constructed to ensure that the control input satisfies the magnitude limits. Subsequently, a robust fault-tolerant controller is developed by using a low-pass filter and an auxiliary system in conjunction with adaptive backstepping design. It is shown that the control algorithm developed not only achieves the stable attitude tracking with prescribed behavioral metrics but also guarantees the boundedness of all the closed-loop signals. Finally, simulation results are given to evaluate the efficacy of the proposed scheme.